Association of Helicobacter pylori Infection with Depression and Anxiety: A Systematic Review and Meta-Analysis - Lu Li; Yadi Ren; Zeyu Wang; Yanqing Niu; Ying Zhao; Xiaherezhati Aihaiti; Yinglan Ji; Man Li (International Journal of Clinical Practice)
Introduction. The association between Helicobacter pylori (H. pylori) infection and depression and anxiety has been reported in the literature. The aim of this meta-analysis is to investigate the association of H. pylori infection with depression and anxiety. Methods. A systematic search was conducted in PubMed, Web of Science, Embase, and Chinese databases for observational studies that reported the incidence or prevalence of depression and anxiety in patients with H. pylori infection. We conducted meta-analysis with a random-effects model. Results. A total of twelve studies were included in this meta-analysis. Significant and positive association was found for H. pylori infection with anxiety (OR 2.49, 95% CI 1.83–3.39), but not depression (OR 1.40, 95% CI 0.75–2.58). Subgroup analysis from study design noted a significant positive association between H. pylori infection and anxiety (case-control and cross-sectional study, OR 2.36, 95% CI 1.65–3.38; cohort study, RR 1.72, 95% CI 1.28–2.32). The similar trend among studies used the Self-Rating Anxiety Scale (OR 2.43, 95% CI 1.78–3.32) and other questionnaires (OR 2.41, 95% CI 1.50–3.87) have been observed. However, subgroup analysis of the association between H. pylori infection and depression yields different results. Subgroup analysis from cohort studies noted a significant association between H. pylori infection and depression (RR 1.99, 95% CI 1.33–2.99), but not case-control and cross-sectional studies (OR 1.20, 95% CI 0.59–2.46). A significant positive association has been observed among studies used the Self-Rating Depression Scale (OR 2.03, 95% CI 1.11–3.70), as opposed to studies using other questionnaires (OR 1.03, 95% CI 0.31–3.44). Conclusion. This meta-analysis provide the support that a significant positive association between H. pylori infection and anxiety disorders. However, the association between H. pylori infection and depression appears to be insignificant.